PERBEDAAN KEPERCAYAAN DIRI BERDASARKAN JENIS KELAMIN REMAJA DI KELURAHAN THE HOK KOTA JAMBI - Muhammad Rai Farhan; Yanto Yanto; Affan Yusra (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Self-confidence is often a problem among adolescents, based on the background of research adolescents have diverse self-confidence. From the results of preliminary data, male adolescents are worried about getting negative assessments from the surrounding environment for performance in doing work, while female adolescents are worried about expressing different opinions to others, thus causing adolescents not confident to be actively involved in community activities, the purpose of this study is to determine whether there are differences in the level of self-confidence of adolescents based on gender. Self-confidence that will be examined is self-confidence, optimistic, objective, responsible, rational, realistic. This study aims to determine differences in self-confidence based on gender in The Hok village, Jambi City. Using quantitative research, with comparative research methods. The study population was 1459 adolescents who were divided into 798 male adolescents and 661 female adolescents, the sampling technique in this study used the Arikunto technique which resulted in 160 samples of male adolescents and 132 samples of female adolescents with a total of 292 samples. Data collection uses a Likert scale, data is analyzed using formula C and different tests through independent sample t-tests. The results of research on Differences in Self-Confidence Based on Adolescent Gender in The Hok Village, Jambi City, the percentage of formula C adolescent boys has a medium percentage of 58.5%, while the percentage of self-confidence of adolescent girls is 63.3% in the high category. The results of the hypothesis test obtained the results of Sig. (2-Tailed) of 0.000 <0.05 and from comparing the t-count and t-table where the t-count value (6.301) > t-table (1.960), the hypothesis is accepted, which means that there are differences in adolescent self-confidence based on gender.